Aran Literasi Baca Tulis Pegon pada Santri Baru di Pondok Pesantren Putri Al-Ma’ruf Juranguluh Mojo Kediri - Ida Maskurun; Muhammad Al Faruq (LP3M IAIFA Kediri, 2020)
In our literacy in the pesantren environment, we must also know literacy in Arabic reading-writing pegon. Because the learner pesantren can not be separated from the name of the Arabic reading-writing pegon. Pegon Arabic is an Arabic script or letter with no symbol, punctuation or sound. According to M. Dahlan that the meaning of pegon is bald Arabic script, or Arabic script used to write Javanese. In the Javanese-Indonesian dictionary, pegon means unable to pronounce. Another word